The Authentic Assessment in An EFL Speaking Classroom at Quwaish English Arabic (QEA) Language Course - Wiratmoko, Gandung; Muamaroh, Muamaroh; Hikmat, Mauly (Research Horizon, 2023)
Speaking is considered by language testers to be the most difficult of the four language skills to assess. This study aims to (1) investigate the model of authentic assessment for speaking skills and (2) explore the implementation of authentic assessment activities in the Speaking Class at the Quwaish English Arabic course in Juwiring, Klaten. The research utilizes a descriptive qualitative method, gathering data through observations and recordings. The study includes three English teachers and sixteen students from various grades as observation samples during the teaching and learning process. The findings of this study conclude that five authentic assessment models are suitable for students at the Quwaish English Arabic course. These models encompass role play, information gap activities, picture talks, brief question and answer sessions, narrating sequences, and pair dialogues.